2009
DOI: 10.1007/s11094-009-0277-0
|View full text |Cite
|
Sign up to set email alerts
|

Developing chromatography-mass spectrometry techniques for quantitative determination of the new original neuroleptic drug dilept

Abstract: Gas chromatography-mass spectrometry (GC-MS) and HPLC-MS techniques have been developed for studying fragmentation and determining the main ion species in the mass spectra of the new original neuroleptic dilept (N-caproyl-L-prolyl-L-tyrosine methyl ester) and its expected metabolites N-caproyl-L-prolyl-L-tyrosine (M1) and N-caproyl-L-proline (M2). Trimethylsilyl derivatives of dilept and its metabolites were analyzed using GC-MS and HPLC-MS in both positive-and negative-ion modes. Retention times were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…We used HPLC-(-)ESI-MS and HPLC-(-)ESI-MS/MS methods that have been previously described [7] to determine dilept and its metabolites in rat blood plasma. It was found that dilept forms a demethylated metabolite upon addition to rat blood plasma.…”
Section: Resultsmentioning
confidence: 99%
“…We used HPLC-(-)ESI-MS and HPLC-(-)ESI-MS/MS methods that have been previously described [7] to determine dilept and its metabolites in rat blood plasma. It was found that dilept forms a demethylated metabolite upon addition to rat blood plasma.…”
Section: Resultsmentioning
confidence: 99%
“…Dry residue was dissolved in 50 μl methanol and analyzed by HPLC-MS/MS (MS: mass spectrometry). Plasma and brain levels of dilept and its metabolite were measured by previously developed HPLC-MS/MS [1]. Penetration through BBB was evaluated by coeffi cient of distribution for the studied compounds (K brain/plasma ).…”
Section: Methodsmentioning
confidence: 99%